The carbonate tectonic units of northern Calabria (Italy): a record of Apulian palaeomargin evolution and Miocene convergence, continental crust subduction, and exhumation of HP-LT rocks. - Reddy, Steven (Geological Society of London, 2007)
In northern Calabria (Italy), the metasedimentary succession of the Lungro?Verbicaro tectonic unit preserves mineral assemblages suggesting underthrusting to depths in excess of 40 km. Internal deformation of these rocks occurred continuously during the following decompression. Index mineral composition associated with progressively younger tectonic fabrics indicates that a substantial part of the structural evolution took place within the blueschist-facies P-T field. Despite their tectonic and metamorphic history, the rocks of the Lungro-Verbicaro Unit preserve significant sedimentary and palaeontological features allowing correlations with successions included in adjacent thrust sheets and the reconstruction of the Mesozoic continental margin architecture. The subduction-exhumation cycle recorded by the Lungro-Verbicaro Unit is entirely of Miocene age. This portion of the Apulia continental palaeomargin was involved in convergence-related deformation not earlier than the Aquitanian. The integration of our results with available constraints on the tectonic evolution of the Apennine-Calabrian Arc system suggests that subduction and most of the subsequent exhumation of the Lungro?Verbicaro Unit occurred, up to Langhian time, at maximum vertical rates in excess of 15 mm a-1. The exhumation process was then completed, at much slower rates (<2 mm a -1) in Late Miocene time, as indicated by both apatite fission-track data and stratigraphic information.